Qualitative Policy Analysis of Hypertension Disease Control at Primary Health Centers in Surakarta, Indonesia - Hastuti, Rini Tri; Dewi, Indri Kusuma; Rachmat, Nur; Setyorini, Yuyun Setyorini; Mulyaningrum, Haryanti Katini; Subagiyo, Didik; Suryaningsih, Anthik Fajar (Journal of Applied Nursing and Health, 2025)
Background: Hypertension is a leading global health issue and a primary risk factor for cardiovascular disease. Despite national strategies in Indonesia, evidence on hypertension control implementation at the district and community levels remains scarce. Surakarta reports hypertension as the most common non-communicable disease (NCD), yet little is known about how policies are translated into practice at primary health centers. Methods: This qualitative descriptive study applied a policy analysis approach, guided by the COREQ reporting standard. Five purposively selected participants (three health workers, one patient, and one district health officer) were interviewed between June and September 2023. Data were collected through in-depth interviews (30–60 minutes) and document reviews, and were analyzed thematically using Creswell’s framework. Results: Three themes emerged: (1) hypertension control policies operationalized at the primary healthcare level and supported by innovations such as BU DESI (Buru Diabetes dan Hipertensi); (2) health promotion through Posbindu PTM and cadre empowerment; and (3) monitoring and evaluation via regular monthly reviews, though patient adherence and multisectoral collaboration remain limited. Conclusion: While hypertension control in Surakarta aligns partially with national strategies, its novelty lies in integrating locally driven innovations such as BU DESI. The study highlights the need to strengthen community empowerment and multisectoral collaboration.